Strategic planning for urban air mobility: Perceptions of citizens and potential users on autonomous flying vehicles - Ferreira, T.; Kalakou, S. (Advances in mobility-as-a-service systems. Advances in Intelligent Systems and Computing, 2020)
World’s current mobility systems are often inefficient and unsustainable, therefore the need for new schemes to satisfy mobility needs appears. This quest has given the impetus to the industry to invest in new technologies such as autonomous systems enabling self-driving vehicles. In this context, the concept of Urban Air Mobility (UAM), a term used for short-distance, on-demand, highly automated, passenger or cargo-carrying air mobility services, has arisen. This paper presents the introduction phase of strategic planning for the era of urban air mobility focusing on user and citizen acceptance of the system required for its operation. A survey is designed to capture the perception of citizens and potential users on aspects such as safety, security, well-being of the society (including issues of aesthetics, quality of life, social impacts), driving behaviour, mobility behaviour, expected benefits and their impact on the acceptance and the intention to use these systems. The acceptance of citizens and potential users (considered as two different groups) is analysed in terms of its potential uses (e.g. health emergencies, leisure, connectivity to remote regions). The survey is applied to the Metropolitan area of Lisbon and 207 responses were gathered. The collected data was analysed through correlation analysis and non-parametric tests. Conclusions are made on perceptions of citizens over different adoption and embracement levels.